Adaptive extended state observer-based flatness nonlinear output control for torque tracking of electrohydraulic loading system. (June 2018) - Jing, Chenghu; Xu, Hongguang; Song, Xiaoming; Lu, Biao
Electrohydraulic loading system is a torque servo system with high-accuracy and high-frequency response. In this paper, an adaptive extended state observer-based flatness nonlinear output control is proposed to improve the torque tracking performance of electrohydraulic loading system. This method combines a flatness concept, expected state, adaptive extended state observer and system output to develop a stable control system. Expected input feedforward based on the flatness property is designed to provide model compensation for bandwidth enhancement. An adaptive extended state observer is proposed to estimate the unmeasured states and the unmodeled dynamics. Based on estimated states and disturbances, state feedback control is developed to ensure the stability of closed-loop system, and to improve torque tracking accuracy and system robustness. The stability of the closed-loop system is proved by the Lyapunov stability theory. Extensive experiments were carried out to verify the performance of high-accuracy tracking of the proposed control strategy.